Stem Cell Therapy in Neuroimmunological Diseases and Its Potential Neuroimmunological Complications - Franz Felix Konen; Philipp Schwenkenbecher; Konstantin Fritz Jendretzky; Stefan Gingele; Lea Grote-Levi; Nora Möhn; Kurt-Wolfram Sühs; Britta Eiz-Vesper; Britta Maecker-Kolhoff; Corinna Trebst; Thomas Skripuletz; Martin W. Hümmert (Cells, 2022)
Background: Since the 1990s, transplantations of hematopoietic and mesenchymal stem cells (HSCT and MSCT) and dendritic cell (DCT) have been investigated for the treatment of neurological autoimmune disorders (NADs). With the growing number of transplanted patients, awareness of neuroimmunolgical complications has increased. Therefore, an overview of SCT for the most common NADs and reports of secondary immunity after SCT is provided. Methods: For this narrative review, a literature search of the PubMed database was performed. A total of 86 articles reporting on different SCTs in NADs and 61 articles dealing with immune-mediated neurological complications after SCT were included. For multiple sclerosis (MS), only registered trials and phase I/II or II studies were considered, whereas all available articles on other disorders were included. The different transplantation procedures and efficacy and safety data are presented. Results: In MS patients, beneficial effects of HSCT, MSCT, and DCT with a decrease in disability and stabilization of disease activity have been reported. These effects were also shown in other NADs mainly in case reports. In seven of 132 reported patients with immune-mediated neurological complications, the outcome was fatal. Conclusions: Phase III trials are ongoing for MS, but the role of SCT in other NADs is currently limited to refractory patients due to occasional serious complications.